Imaging for precision medicine: can V‐P SPECT measure mepolizumab response in asthma?. Issue 3 (1st February 2021) - McDonald, Vanessa M.; Urroz, Paola D.; Bajc, Marika; Rutherford, Natalie; Brooker, Bree; Gibson, Peter G.
Abstract: Monoclonal antibody therapies are effective for many but not all people with severe asthma. Precision medicine guides treatment selection using biomarkers to select patients most likely to respond according to their inflammatory endotypes. However, when assessing response to treatment, greater precision is required. We report a case series describing treatment response to mepolizumab in four severe asthma patients, assessed by traditional methods and with objective ventilation/perfusion single photon emission computed tomography (V‐P SPECT). In this series, patients with severe asthma received mepolizumab treatment with clinical outcomes recorded at commencement and at approximately 16 weeks post‐treatment initiation. V‐P SPECT imaging was performed before and after treatment to determine ventilation heterogeneity and perfusion, and its ability to assess treatment responsiveness. V‐P SPECT shows promise as an objective measure to assess lung ventilation and perfusion to observe and assess responsiveness to mepolizumab. With quantification, this measure may allow better precision in determining treatment improvements. Abstract : We report a case series describing treatment response to mepolizumab in four severe asthma patients, assessed by traditional methods and with objective ventilation/perfusion single photon emission computed tomography (V‐P SPECT). In this series, patients with severe asthma received mepolizumab treatment with clinical outcomes recorded and V‐P SPECT imaging performed at commencement and at approximately 16 weeks post‐treatment initiation. V‐P SPECT shows promise as an objective measure to assess lung ventilation and responsiveness to mepolizumab, allowing better precision in determining treatment improvements.